Lateral Quadratus Lumborum Block versus Transversus Abdominis Plane Block in Laparoscopic Surgery: A Randomized Controlled Study - Omar Sayed Fargaly; Maged Labib Boules; Mohamed Ahmed Hamed; Mohammed Abdel Aleem Abbas; Mohammed Ahmed Shawky (Anesthesiology Research and Practice)
Background. After laparoscopic abdominal surgery, we aim to evaluate the analgesic efficiency of US-directed bilateral transversus abdominis plane block (TAPB) and quadratus lumborum block (QLB). Methods. 50 patients aged 18–60 years listed for elective laparoscopic abdomen operation were registered in this study. Cases were randomly allocated into two similar groups: TAPB and QLB groups. The first outcome was the growing morphine consumption on the 1st day postoperatively. The second outcome involved VAS score, first analgesic necessities, and any postoperative complications. Statistical analysis was done with the 2-sample t-test, and Mann–Whitney U testing was utilized to compare medians for skewed end points. Qualitative data were introduced as numbers and percentages, and chi-squared testing was utilized to determine the significance. Results. The median cumulative morphine consumptions on the 1st day were high significantly in the TAPB group than in the QLB group (6 mg [6, 9] vs. 3 mg [3, 6], p value ≤0.0001]). The QLB group showed an increase in the median of the time to the first analgesic request in comparison with the TAPB group (17 hours [12, 24] vs. 8 hours [6, 24], p≤0.001). In addition, on the 1st day, the mean VAS scoring at rest was lower in the QLB group. Conclusion. In comparison to the TAPB, the QL block delivers more successful pain relief, has an extended period of analgesic actions, extends interval to the 1st analgesic necessity, is accompanied with lesser morphine consumptions, and may be utilized in multimodal analgesia and opioid-sparing regimens after that laparoscopic operation. This trial is registered with NCT04553991.